Comparative study : Information revelation, users behaviour and awareness of privacy on social networking sites / Norhailawati Misran - Misran, Norhailawati (2014)
Social networking sites (SNS) or some of the researches called as web based social network have become vast online communication recently and the most popular online activity worldwide. The social networking sites require users to give their personal information during registration to the site. Without realizing, users expose their personal information to the entire network. The study is used to identify the types of information reveal, social network sites behavior / habit and privacy awareness among different generation: The Baby Boomers, Generation X and Generation Y. The findings of this study prove that the types of information revealed are similar between the three generations, though the behaviour / habit towards the participation in social network sites and privacy awareness are different. Several criterion used as guidance to identify the generations behaviour / habit such as the duration spent in social network sites, the time spent per session in social network sites, the number of friend they have, how often they check their account (log in frequency) and how often they alter their status. The Baby Boomers generation shows that basically they had spent about 1 to 3 years in the site, surf the site about less than 2 hours in a day, have less than 250 friends in the network sites, intent to alter their status once every few days and basically they log in to the sites once in a day. The Generation X had spent their time in social networking sites about 3 to 5 years, use less than 2 hours in a day to surf the sites, connected to more than 250 friends, rarely update their status online and usually log in to the sites once in a day. Meanwhile the Generation Y had spent 3 to 5 years in social network sites, surf the site about less than 2 hours in a day, had more than 250 friends attached to them in the sites, likes to alter their status more than once a day and the frequency log in is either twice or three times in a day. About privacy awareness, all generations show that they aware on the privacy awareness (the privacy setting and visibility of the information) but the Gen X and Gen Y show the most.